Relationship between socio-emotional difficulties with 24-hour movement behavior and other factors among preschools children in Kelantan, Malaysia - Rahim, Mohamad Hazni Abd (2023)
Introduction: Children's mental health disorders are a serious concern, and adherence to the 24-H movement behaviour guidelines is one of the contributing factors. Measuring movement behaviour such as physical activity, sedentary behaviour, and sleep time throughout 24 hours is critical for assessing early childhood development. Therefore, this study aims to identify socioemotional problems and associated factors among preschool children and determine the association between adherence to 24-hour movement behaviour guidelines and socioemotional problems in the same target group in Kelantan, Malaysia. Methods: This study was conducted in two phases. The first phase was a cross-cultural adaptation of the movement behaviour questionnaire (MBQ). The original version of MBQ contains a 15-item short-form instrument for measuring preschool children's physical activity, screen time, and sleep. Permission was granted to translate into Malay version using a ten-step process. Ten independent experts were involved in the content validity process, while thirty parents of children aged four to six were selected for face validation. The second phase was conducted from November to December 2022 using a cross-sectional design with a sample size of 612 preschools determined using the single proportion formula. All participants were selected from 18 public and private preschools using a multistage random sampling technique. All eligible parents of children aged four, five, and six were contacted, and each preschool was required to enrol an average of 34 children. The self-administered proxy report Malay validated questionnaire was used. The data was analysed using SPSS ver 26. As for phase one, the content validity ratio (CVR), content validity index (CVI), modified kappa agreement and face validity index (FVI) were reported; for phase two, the data was analysed using logistic and linear regression. Results: The content validation of the experts' ratings and responses revealed that the MBQ-M contained significant and essential questions. All remaining MBQ-M items had a CVR greater than 0.62. I-CVI scores of 0.95 for relevance, 0.93 for clarity, 0.95 for simplicity, and 0.93 for ambiguity indicated adequate and acceptable content validity. The face validity index of clarity and comprehension were 0.95 and 0.93, respectively, indicating a satisfactory and acceptable level. Of the 612 questionnaires distributed, 557 (91%) parents consented to participate in the study and completed the form. The average Children's age was 70.19 months; 52.1% were boys, 56.7% were 6 years old, and 66.6% of parents' respondents were female. The estimated prevalence of socio-emotional problems was 8.4%, and peer problem was the most prevalent attribute (19.7%.). Girls, one parent working, at least two siblings, and single-parent families were associated with socio-emotional problems. The percentage of met guidelines for physical activity was 42.2%, screen time 65.5%, sleep duration 70.3% and only 17.6% adhered to all three guidelines. Children in preschool do not meet individual screen time guidelines, and the specific combination of screen time and physical activity was associated with increased socioemotional problems, including emotional symptoms, conduct problems, and hyperactivity (p<0.05). In addition, a specific combination of screen time and sleep guidelines and a general combination of at least two or three guidelines was associated with emotional symptoms among preschools (p<0.05) after adjusting for child and parent socio-demographics. Conclusions: Socioemotional problems remain a significant concern, with peer problems as a top priority for stakeholders. Only one in ten preschools children meet the recommended 24-hour movement behaviour guidelines. Non-adherence, screen time and physical inactivity guidelines are linked to more serious socioemotional difficulties like emotional symptoms, conduct problems and hyperactivity. Early inappropriate intervention during early childhood can impact a child's healthy development. This highlights the importance of policy initiatives and health promotion programs for preschoolers to encourage healthy 24-h movement behaviours.